Determination of the Cost of Goods Production Based on the Full Costing Method in the Soppeng Typical Souvenir Culinary Business - Anugrah, Muhammad; Rijal, Abdul; Syachbrani, Warka (Phinisi Applied Accounting Journal, 2024)
This research aims to: determine and analyze the Determination of Cost of Goods Production Based on the Full Costing Method (Case Study of Tape An-nur Micro, Small and Medium Enterprises in Soppeng Regency). The sample used in this research is data and information on daily costs during January 2024 at Tape An-nur Micro, Small and Medium Enterprises. Based on the results of the research: (1) The cost of production that has been carried out by researchers shows that the cost of production for the UMKM Tape An-nur product is IDR 16,914 for the Tape product, IDR 36,214 for the peeled peanut product, IDR 17,414 for the Bolu Cukke product , IDR 15,814 for Jipang products, and IDR 16,854 for Cumin Crackers products. Meanwhile, the selling price set by the company is IDR 25,000 for Tape and Bolu Cukke, IDR 20,000 for Jipang and Cumin Crackers, IDR 50,000 for Peeled Nuts. (2) Looking at the comparison between the cost of production and the selling price of the product, the business owner makes a profit of IDR 8,086 on Tape products, IDR 13,786 on Peeled Peanut products, IDR 5,586 on Bolu Cukke products, IDR 4,168 on Jipang products, and Rp. 3,146 on cumin crackers products.Penelitian ini bertujuan untuk: mengetahui dan menganalisis Penentuan Harga Pokok Produksi Berdasarkan Metode Full Costing (Studi Kasus pada Usaha Mikro Kecil dan Menengah Tape An-nur di Kabupaten Soppeng). Sampel yang digunakan dalam penelitian ini adalah data dan informasi biaya perhari selama bulan Januari 2024 pada Usaha Mikro Kecil dan Menengah Tape An-nur. Berdasarkan hasil penelitian bahwa: (1) Harga Pokok Produksi yang telah dilakukan peneliti menunjukan bahwa harga pokok produksi pada produk UMKM Tape An-nur Sebesar Rp16.914 pada produk Tape, Rp36.214 pada produk Kacang kupas, Rp17.414 pada Produk Bolu cukke, Rp15.814 pada produk Jipang, dan Rp16.854 pada produk Kerupuk jintan Sedangkan harga jual yang ditetapkan oleh perusahaan sebesar Rp25.000 untuk Tape dan Bolu cukke, Rp20.000 untuk Jipang dan Kerupuk jintan, Rp50.000 untuk Kacang kupas. (2) Melihat perbandingan antara harga pokok produksi dengan harga jual produk membuat pemilik usaha memperoleh laba sebesar Rp8.086 pada produk Tape, Rp13.786 pada produk Kacang kupas, Rp5.586 pada produk Bolu cukke, Rp4.168 pada produk Jipang, dan Rp3.146 pada produk Kerupuk jintan.